CD16+ Monocyte Subset Was Enriched and Functionally Exacerbated in Driving T-Cell Activation and B-Cell Response in Systemic Lupus Erythematosus - Zhu, Huaqun; Hu, Fanlei; Sun, Xiaolin; Zhang, Xiaoying; Zhu, Lei; Liu, Xu; Li, Xue; Xu, Liling; Shi, Lianjie; Gan, Yuzhou; Su, Yin (Frontiers in Immunology, 2016)
Background The roles that CD16+ monocyte subset plays in T-cell activation and B-cell response have not been well studied in systemic lupus erythematosus (SLE). Objective The present study aimed to investigate the distribution of CD16+ monocyte subsets in SLE and explore their possible roles in T-cell activation and B-cell differentiation. Methods The frequencies of monocyte subsets in the peripheral blood of healthy controls (HCs) and patients with SLE were determined by flow cytometry. Monocyte subsets were sorted and cocultured with CD4+ T cells and CD19+ B cells. Then, T and B cells were collected for different subset detection, while the supernatants were collected for immunoglobulin G, IgA, and IgM or interferon-γ and interleukin-17A detection by enzyme-linked immunosorbent assay. Results Our results showed that CD16+ monocytes exhibited a proinflammatory phenotype with elevated CD80, CD86, HLA-DR, and CX3CR1 expression on the cell surface. It’s further demonstrated that CD16+ monocytes from patients and HCs shared different cell-surface marker profiles. The CD16+ subset was enriched in SLE and had an exacerbated capacity to promote CD4+ T cell polarization into a Th17 phenotype. Also, CD16+ monocytes had enhanced impacts on CD19+ B cells to differentiate into plasma B cells and regulatory B cells with more Ig production. Conclusion This study demonstrated that CD16+ monocytes, characterized by different cell-surface marker profiles, were enriched and played a critical role in driving the pathogenic T- and B-cell responses in patients with SLE.